Ferramentas de IA Generativas de Textos na Educação Básica: Uma perspectiva docente - Rosa, Marcus G. L. da; Mendes, Ricardo D.; Oliveira, Winy G. S. de; Martins, Luan A.; Souza, André S. de; Carvalho, João M.; Vieira, Alex S. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2025)
This work presents the experiences gained during a workshop in the Amazon region, aimed at training public basic education teachers in the use of artificial intelligence tools for text generation. The study employed the methodology of action research, exploring theoretical concepts and demonstrating freely available tools. The results indicated a positive impact of AI on basic education. Additionally, most of the 47 teachers reported greater efficiency in preparing teaching materials and considered that AI contributes to a more inclusive and dynamic education in the teaching-learning process.